Oculo‐zygomatic nerve transfer for facial synkinesis: An anatomical feasibility study. Issue 7 (8th April 2019) - Jensson, David; Weninger, Wolfgang J.; Schmid, Melanie; Meng, Stefan; Jonsson, Lars; Tzou, Chieh‐Han John; Rodriguez‐Lorenzo, Andres
Abstract: Background: Patients with severe oro‐ocular synkinesis often present with concomitant inefficient smile excursion on the affected site. In theory, oculo‐zygomatic nerve transfer may decrease synkinesis and improve smile by redirecting nerve fibers to their target muscle. The aim of this study was to explore the feasibility of nerve transfer in human cadavers between a caudal branch innervating the orbicularis oculi to a cephalad branch innervating the zygomaticus major muscles. Methods: Eighteen hemi‐faces were dissected. Reach for direct coaptation of a caudal nerve branch innervating the orbicularis oculi muscle to a cephalad nerve branch innervating the zygomaticus major muscle was assessed. Measurements included total number of nerve branches as well as maximum dissection length. Nerve samples were taken from both branches at the site of coaptation and histomorphometric analysis for axonal count was performed. Results: The number of sub‐branches to the orbicularis oculi muscle was 3.1 ± 1.0 and to the zygomaticus major muscle 4.7 ± 1.2. The maximal length of dissection of the caudal nerve branch to the orbicularis oculi muscle was 28.3 ± 7.3 mm and for the cranial nerve branch to the zygomaticus major muscle 23.8 ± 6.5 mm. Transection and tension‐free coaptation was possible in all cases but one. The average myelinated fiber counts per mm 2 was of 5, 173 ± 2, 293 for the caudal orbicularis oculi branch and 5, 256 ± 1, 774 for the cephalad zygomaticus major branch. Conclusion: Oculo‐zygomatic nerve transfer is an anatomically feasible procedure. The clinical value of this procedure, however, remains to be proven.